Arbutus unedo L. and Ocinum basilicum L. as sources of natural ingredients for bread functionalization - Sallawi, Takwa (2018)
The overwhelming growth of the world population is causing direct consequences on food demands, which has forced the food industry to apply synthetic additives in order to meet the needs of the consumer and ensuring the global quality of the food products including aspect, texture and flavor. However, due to the publication of some studies describing adverse effects associated with these synthetic additives, the natural ones have been gaining increasing interest. Arbutus unedo L. (strawberry tree) fruits and Ocimum basilicum L. (basil) leaves, are important sources of bioactive natural molecules, especially phenolic compounds, including flavan-3- ols and phenolic acids, respectively . The aim of this work was to demonstrate the antioxidant potential (free radical scavenging effect, reducing power and inhibition of lipid peroxidation) and the absence of toxicity (porcine liver primary cells) of ethanol extracts, obtained from the previously mentioned plants by using optimal conditions. Subsequently, the extracts were incorporated as natural ingredients in loaf bread samples, with two objectives: to functionalize loaf bread, introducing bioactive properties; and as natural ingredients with preservation capacity. Five groups of loaf bread samples were prepared: i) control (without natural or synthetic additives); ii) loaf bread incorporated with strawberry tree extract; iii) loaf bread incorporated with basil extract; iv) loaf bread incorporated with ascorbic acid- E300 (natural additive); and v) loaf bread incorporated with potassium sorbate- E202 (synthetic additive). Both extracts (strawberry tree fruits and basil leaves) presented antioxidant activity (EC50 values lower the 595 and 351 μg/mL, respectively), without toxicity up to the maximal tested dose, and the main compounds present were (+)-catechin and rosmarinic acid, respectively. The introduction of both natural and synthetic additives in loaf bread when compared to the control sample, did not cause significant changes, neither in pH values, nor in color or any of the evaluated nutritional parameters. The obtained results demonstrate that these extracts could be used in the development of new loaf bread replacing the synthetic preservatives, without interfering with the physical and nutritional characteristics.